Method for preparing Portland cement from iron ore tailing mud and desulfurized gypsum
Through the combination of iron ore tailing sludge, desulfurization gypsum and nanocrystalline core suspension, the problems of unstable flexural and compressive resistance and long settling time of silicate cement are solved, and high-strength, safe and reliable silicate is achieved Cement preparation improves resource utilization and environmental protection effect.
Patent Information
- Application Number
- CN202411279025.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-12
AI Technical Summary
In the prior art, the preparation of silicate cement by iron ore tailing sludge has problems such as unstable cement flexural resistance, long settling time, easy to produce floating powder and heavy metal dissolution, which affects resource utilization and environmental protection.
Using the combination method of iron ore tailing mud, desulfurization gypsum and nanocrystalline core suspension, silicate cement is prepared through specific proportions and process flow to form a high-strength spatial network microstructure, improve flexural and compressive strength, and shorten condensation. time.
It improves the flexural compressive strength of silicate cement, shortens the settling time, improves the cement's settling efficiency, ensures the safety and efficient application of the product, reduces the dissolution of heavy metal ions, and complies with environmental protection standards.
Smart Images

Figure BDA0005041079370000071 
Figure BDA0005041079370000072 
Figure BDA0005041079370000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicate cement, and in particular to a method for preparing silicate cement by utilizing iron ore tailings and desulfurized gypsum. Background Art
[0002] The storage of iron ore tailings not only has a low resource utilization rate, but also poses a great threat to the surrounding environment. Therefore, research on the comprehensive utilization of iron ore tailings resources is of great significance for improving resource utilization and environmental protection. At present, the simplest and most feasible methods for the management and utilization of tailings are: one is to cover the soil and create fields. In areas where the soil is relatively sufficient, the method of pressing 10-20 cm of soil and then planting, covering the soil and creating fields, and expanding the cultivated land area can be adopted. This method is suitable for valley-shaped tailings ponds. This method can cause secondary hazards of dust due to the thin soil layer. Secondly, it is to make full use of organic organisms and select substances in the degradable solidified waste to absorb mine tailings. It overcomes the disadvantages of using a large amount of soil layer and the inconvenience of management due to the shape of the tailings, but there is a phenomenon of low degradation rate. Using iron ore tailings to prepare silicate cement is a good method for recycling iron ore tailings. However, it has the following problems: (1) The existing technology uses iron ore tailings to make silicate cement mixed materials, but the flexural and compressive properties of cement are unstable; (2) The coagulation time of silicate cement made from iron ore tailings is relatively long, making the preparation process less efficient; (3) silicate cement is prone to produce floating powder, and long-term use will cause a large amount of heavy metals to dissolve, which is easy to cause damage to the surrounding environment. To this end, the present invention provides a method for preparing silicate cement using iron ore tailings and desulfurized gypsum Summary of the invention
[0003] In view of this, the present invention proposes a method for preparing silicate cement by utilizing iron ore tailings and desulfurized gypsum.
[0004] The technical solution of the present invention is achieved in this way:
[0005] A method for preparing silicate cement by using iron ore tailings and desulfurized gypsum comprises the following raw materials in parts by weight: 30-50 parts of cement clinker, 30-40 parts of iron ore tailings powder, 10-15 parts of nanocrystalline core suspension and 5-8 parts of desulfurized gypsum.
[0006] The preparation of nanocrystalline core suspension includes the following steps:
[0007] S1. The raw material Ca(NO 3 ) 2 and Mg(NO 3 ) 2 Mix, add potassium nitrate solution, stir, mix, and drop polycarboxylate water reducer to obtain mixture I;
[0008] S2. The raw material Na2 SiO 3 Add potassium nitrate solution, stir, mix, and drop polycarboxylate water reducer to obtain mixture II;
[0009] S3. Mix the mixture I and the mixture II, and adjust the pH value to obtain a nanocrystalline core suspension.
[0010] Furthermore, the volume concentration of the potassium nitrate solution is 10-15%, and the Ca(NO 3 ) 2 Mg(NO 3 ) 2 and Na 2 SiO 3 The mass ratio is (8-10):(3-5):(6-8).
[0011] Furthermore, the polymer HOOC-CH 2 -CH(COOH)-(CH 2 -COONa)-CH 2 The content of -COOH is 75-90%.
[0012] Furthermore, the stirring is magnetic stirring, the stirring speed is 200-230 rpm, the temperature is 15-25° C., and the time is 25-35 min; and the adjusted pH value is 11.5-11.8.
[0013] Furthermore, the nanocrystalline core suspension has a Ca / Si ratio of 0.6-0.9 and a Mg / Si ratio of 0.04-0.06.
[0014] Furthermore, the cement clinker is composed of CaO, SiO in a mass ratio of (60-65):(15-20):(3-6):(2-5). 2 、Al 2 O 3 and Fe 2 O 3 composition.
[0015] Furthermore, the iron ore tailings are stirred, heated and crushed and ground. The iron ore tailings are heated to 780-810°C at 10-15°C / min for 3-3.5h, then cooled to room temperature for grinding. The particle size after grinding is <80μm, and the residue after passing through a 200-mesh sieve is <3%.
[0016] Furthermore, the cement clinker, iron ore tailings powder and desulfurized gypsum are mixed and ground, and the grinding time is 15-20 minutes.
[0017] A method for preparing silicate cement using iron ore tailings and desulfurized gypsum, comprising the following steps: mixing cement clinker, iron ore tailings powder, desulfurized gypsum and nanocrystalline core suspension with a specific surface area of 300-400m 2 / kg, we get silicate cement.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The silicate cement prepared by the raw materials, proportions and methods of the present invention is safe and reliable, and can simultaneously improve the flexural strength and compressive strength of cement, thereby obtaining high-strength silicate cement, which is better applied to concrete engineering. Among them, the nanocrystalline core suspension material prepared by the present invention using a certain proportion of raw materials and proportions is compounded with cement clinker, iron ore tailings powder and desulfurized gypsum to form a better spatial network microstructure, shorten the initial setting time and the final setting time, improve the coagulation efficiency of cement, and achieve the application effect of silicate cement's flexural and compressive resistance. DETAILED DESCRIPTION
[0020] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0021] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0022] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0023] Polycarboxylate water reducer was purchased from Guizhou Wanqian Building Materials Co., Ltd. The iron ore tailings powder comes from the iron ore tailings of Shilu Iron Mine in Changjiang, Hainan.
[0024] Example 1
[0025] A method for preparing silicate cement using iron ore tailings and desulfurized gypsum, comprising the following raw materials in parts by weight: 35 parts of cement clinker, wherein the cement clinker is composed of CaO, SiO2 and MgO2 in a mass ratio of 60:15:3:2; 2 、Al 2 O 3 and Fe 2 O 3 Composition: 30 parts of iron ore tailings powder, 15 parts of nanocrystalline core suspension, and 5 parts of desulfurized gypsum. The production process of silicate cement includes the following steps: heating the iron ore tailings to 780°C at 10°C / min, keeping the temperature for 3 hours, then cooling it to room temperature for grinding. The particle size after grinding is 70μm and passes through a 200-mesh sieve. Mixing and grinding the cement clinker, ground iron ore tailings powder and desulfurized gypsum for 15 minutes. Mixing the sieved cement clinker, iron ore tailings powder, desulfurized gypsum and nanocrystalline core suspension. The specific surface area of the mixture is 350m2 / kg, we get silicate cement.
[0026] The preparation of nanocrystalline core suspension includes the following steps:
[0027] Step (1): The raw material Ca(NO 3 ) 2 、Na 2 SiO 3 and Mg(NO 3 ) 2 Weigh according to the mass ratio of 9:7:4, prepare a 12% potassium nitrate solution, the polymer HOOC-CH 2 -CH(COOH)-(CH 2 -COONa)-CH 2 The content of -COOH is 80%.
[0028] Step (2) Raw material Ca(NO 3 ) 2 and Mg(NO 3 ) 2 Add potassium nitrate solution to the mixture, stir, mix, and drop polycarboxylate water reducer to obtain mixture I;
[0029] Step (3): The raw material Na 2 SiO 3 Add potassium nitrate solution, stir, mix, and drop polycarboxylate water reducer to obtain mixture II;
[0030] Step (4): Mixing mixture I and mixture II, and stirring them. After mixing, magnetic stirring is performed at a speed of 200 rpm, a temperature of 20° C., and a time of 30 min. After stirring, the pH value is adjusted to 11.7, and stirring is continued to obtain a nanocrystalline core suspension, wherein Ca / Si is 0.8 and Mg / Si is 0.05.
[0031] Example 2
[0032] A method for preparing silicate cement using iron ore tailings and desulfurized gypsum, comprising the following raw materials in parts by weight: 50 parts of cement clinker, wherein the cement clinker is composed of CaO, SiO2 and MgO2 in a mass ratio of 65:20:6:5. 2 、Al 2 O 3 and Fe 2 O 3Composition: 40 parts of iron ore tailings powder, 10 parts of nanocrystalline core suspension, and 8 parts of desulfurized gypsum. The production process of silicate cement includes the following steps: heating the iron ore tailings to 810°C at 12°C / min, keeping the temperature for 3.2 hours, then cooling it to room temperature for grinding. The particle size after grinding is 75μm and passes through a 200-mesh sieve. Mixing and grinding the cement clinker, ground iron ore tailings powder and desulfurized gypsum for 20 minutes. Mixing the sieved cement clinker, iron ore tailings powder, desulfurized gypsum and nanocrystalline core suspension. The specific surface area of the mixture is 350m 2 / kg, we get silicate cement.
[0033] The preparation of nanocrystalline core suspension includes the following steps:
[0034] Step (1): The raw material Ca(NO 3 ) 2 、Na 2 SiO 3 and Mg(NO 3 ) 2 Weigh according to the mass ratio of 10:6:3, prepare a 12% potassium nitrate solution, the polymer HOOC-CH 2 -CH(COOH)-(CH 2 -COONa)-CH 2 The content of -COOH is 80%.
[0035] Step (2) Raw material Ca(NO 3 ) 2 and Mg(NO 3 ) 2 Add potassium nitrate solution to the mixture, stir, mix, and drop polycarboxylate water reducer to obtain mixture I;
[0036] Step (3): The raw material Na 2 SiO 3 Add potassium nitrate solution, stir, mix, and drop polycarboxylate water reducer to obtain mixture II;
[0037] Step (4): Mixing mixture I and mixture II, stirring, and then subjecting the mixture to magnetic stirring at a speed of 220 rpm, a temperature of 25° C., and a time of 25 min. After stirring, adjusting the pH value to 11.6, and continuing to stir to obtain a nanocrystalline core suspension, wherein Ca / Si is 0.6 and Mg / Si is 0.04.
[0038] Example 3
[0039] A method for preparing silicate cement using iron ore tailings and desulfurized gypsum, comprising the following raw materials in parts by weight: 40 parts of cement clinker, wherein the cement clinker is composed of CaO, SiO2 and MgO2 in a mass ratio of 62:17:4:5;2 、Al 2 O 3 and Fe 2 O 3 Composition: 35 parts of iron ore tailings powder, 14 parts of nanocrystalline core suspension, and 6 parts of desulfurized gypsum. The production process of silicate cement includes the following steps: heating the iron ore tailings to 800°C at 12°C / min, keeping the temperature for 3.5 hours, then cooling it to room temperature for grinding. The particle size after grinding is 70μm and passes through a 200-mesh sieve. Mix and grind the cement clinker, ground iron ore tailings powder and desulfurized gypsum for 20 minutes. Mix the sieved cement clinker, iron ore tailings powder, desulfurized gypsum and nanocrystalline core suspension. The specific surface area of the mixture is 350m 2 / kg, we get silicate cement.
[0040] The preparation of nanocrystalline core suspension includes the following steps:
[0041] Step (1): The raw material Ca(NO 3 ) 2 、Na 2 SiO 3 and Mg(NO 3 ) 2 Weigh according to the mass ratio of 9:6:3, prepare a potassium nitrate solution with a volume concentration of 14%, and the polymer HOOC-CH 2 -CH(COOH)-(CH 2 -COONa)-CH 2 The content of -COOH is 80%.
[0042] Step (2) Raw material Ca(NO 3 ) 2 and Mg(NO 3 ) 2 Add potassium nitrate solution to the mixture, stir, mix, and drop polycarboxylate water reducer to obtain mixture I;
[0043] Step (3): The raw material Na 2 SiO 3 Add potassium nitrate solution, stir, mix, and drop polycarboxylate water reducer to obtain mixture II;
[0044] Step (4): Mixing mixture I and mixture II, and stirring them. After mixing, magnetic stirring is performed at a speed of 230 rpm, a temperature of 15-25° C., and a time of 35 min. After stirring, the pH value is adjusted to 11.8, and stirring is continued to obtain a nanocrystalline core suspension, wherein Ca / Si is 0.9 and Mg / Si is 0.06.
[0045] Comparative Example 1
[0046] The difference between Comparative Example 1 and Example 1 is that the raw material of nanocrystalline core suspension is removed from the raw materials of Portland cement, and other raw materials and preparation methods remain unchanged.
[0047] Comparative Example 2
[0048] The difference between Comparative Example 2 and Example 1 is that the potassium nitrate solution, a raw material for preparing the nanocrystalline core suspension, is replaced by an equal amount of potassium silicate solution, and other raw materials and preparation methods remain unchanged.
[0049] Comparative Example 3
[0050] The difference between Comparative Example 3 and Example 1 is that the polymer HOOC-CH 2 -CH(COOH)-(CH 2 -COONa)-CH 2 The content of -COOH was replaced by 50%, and the other raw materials and preparation methods remained unchanged.
[0051] Comparative Example 4
[0052] The difference between Comparative Example 3 and Example 1 is that the pH adjustment step is removed, the volume concentration of the potassium nitrate solution is replaced with 7%, and other raw materials and preparation methods remain unchanged.
[0053] Comparison example:
[0054] Commercially available silicate cement was used as a control example and was purchased from Hainan Xinda Cement Products Co., Ltd.
[0055] test
[0056] For the silicate cement prepared by the methods of Examples 1-3 and Comparative Examples 1-4, according to the requirements of GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", GB / T 1346-2011 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency" and GBT 176-2017 "Cement Chemical Analysis Method", the flexural strength (MPa) and compressive strength (MPa) were measured on the 5th and 25th days respectively, and the setting time, including the initial setting time and the final setting time, was recorded (Table 1). The test results show that the flexural strength and compressive strength of the silicate cement prepared by the methods of Examples 1-3 on the 5th and 25th days are higher than those of Comparative Examples 1-4. At the same time, the silicate cement prepared by the methods of Examples 1-3 shortens the initial setting time and the final setting time, and improves the setting efficiency of the cement.
[0057] According to the solid waste leaching toxicity determination method (HJ / T 299-2007), the product was subjected to leaching toxicity test, and the heavy metal dissolution was detected by ICP method. The results are shown in Table 2. The heavy metal ion leaching concentration conforms to GB5085.3-2007 "Hazardous Waste Identification Standard - Leaching Toxicity Identification".
[0058] Table 1
[0059]
[0060] Table 2
[0061]
[0062]
[0063] Test results: The present invention uses cement clinker, iron ore tailings powder, and nanocrystalline core suspension desulfurized gypsum to prepare silicate cement, wherein the polymer HOOC-CH 2 -CH(COOH)-(CH 2 -COONa)-CH 2 -COOH content is 75-90%, pH value is adjusted to 11.5-11.8, Ca / Si in the prepared nanocrystalline core suspension is 0.6-0.9, Mg / Si is 0.04-0.06. The silicate cement prepared by the methods of Examples 1-3 of the present invention effectively improves the flexural strength. The flexural strength tests on the 5th and 25th days show that the flexural strength of the silicate cement prepared by Examples 1-3 is higher than that of Comparative Examples 1-4, and higher than the positive control. At the same time, the compressive strength of the silicate cement on the 5th and 25th days is also improved. When the raw material ratio or preparation method is changed in Comparative Examples 1-4, the quality of the silicate cement is reduced by removing the raw material nanocrystalline core suspension or changing the composition of the polymer in the polycarboxylic acid water reducer. Therefore, the silicate cement prepared by the raw materials, raw material ratio and preparation method of the present invention is safe to use, has high coagulation efficiency, and has the application effects of flexural and compressive resistance.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing silicate cement using iron ore tailings and desulfurized gypsum, characterized in that: The method comprises the following raw materials in parts by weight: 30-50 parts of cement clinker, 30-40 parts of iron ore tailings powder, 10-15 parts of nanocrystalline core suspension and 5-8 parts of desulfurized gypsum.
2. The method for preparing silicate cement by utilizing iron ore tailings and desulfurized gypsum according to claim 1, characterized in that: The preparation of the nanocrystal core suspension comprises the following steps: S1. The raw materials Ca (NO3) 2 and Mg (NO3) 2 are mixed, potassium nitrate solution is added, stirred, mixed, and polycarboxylate water reducer is added dropwise to obtain a mixture Ⅰ; S2. The raw material Na2SiO3 is added to the potassium nitrate solution, stirred, mixed, and a polycarboxylate water reducer is added dropwise to obtain a mixture II; S3. Mix the mixture I and the mixture II, and adjust the pH value to obtain a nanocrystalline core suspension.
3. A method for preparing silicate cement using iron ore tailings and desulfurized gypsum according to claim 2, characterized in that: The volume concentration of the potassium nitrate solution is 10-15%, and the mass ratio of Ca(NO3)2, Mg(NO3)2 and Na2SiO3 is (8-10):(3-5):(6-8).
4. A method for preparing silicate cement using iron ore tailings and desulfurized gypsum according to claim 2, characterized in that: The content of the polymer HOOC-CH2-CH(COOH)-(CH2-COONa)-CH2-COOH in the polycarboxylate water-reducing agent is 75-90%.
5. The method for preparing silicate cement by utilizing iron ore tailings and desulfurized gypsum according to claim 2, characterized in that: The stirring is magnetic stirring, the stirring speed is 200-230rpm, the temperature is 15-25°C, and the time is 25-35min; the pH value is adjusted to 11.5-11.
8.
6. The method for preparing silicate cement by utilizing iron ore tailings and desulfurized gypsum according to claim 2, characterized in that: S3, the nanocrystal core suspension, Ca / Si is 0.6-0.9, Mg / Si is 0.04-0.
06.
7. The method for preparing silicate cement by using iron ore tailings and desulfurized gypsum according to claim 1, characterized in that: The cement clinker is composed of CaO, SiO2, Al2O3 and Fe2O3 in a mass ratio of (60-65):(15-20):(3-6):(2-5).
8. The method for preparing silicate cement by using iron ore tailings and desulfurized gypsum according to claim 1, characterized in that: The iron ore tailings are stirred, heated and crushed and ground. The iron ore tailings are heated to 780-810° C. at 10-15° C. / min for 3-3.5 hours, then cooled to room temperature for grinding. The particle size after grinding is <80 μm, and the residue after passing through a 200-mesh sieve is <3%.
9. The method for preparing silicate cement by using iron ore tailings and desulfurized gypsum according to claim 1, characterized in that: The cement clinker, iron ore tailings powder and desulfurized gypsum are mixed and ground, and the grinding time is 15-20 minutes.
10. A method for preparing silicate cement using iron ore tailings and desulfurized gypsum according to any one of claim 19, characterized in that: The production process includes the following steps: mixing cement clinker, iron ore tailings powder, desulfurized gypsum and nanocrystalline core suspension with a specific surface area of 300-400m 2 / kg, we get silicate cement.
Citation Information
Patent Citations
Preparation method for Portland cement with iron tailings
CN104150794A
Fast-setting-and-hardening belite sulphate aluminum cement clinker, applications and production technology
CN104860556A
Hydrated calcium silicate nanocrystalline nucleus suspension and preparation method thereof
CN112010581A
Polysaccharide-modified hydrated calcium aluminosilicate nano crystalline nucleus suspension and preparation method thereof
CN112094072A
Calcium silicate hydrate crystal nucleus early strength agent and preparation method thereof
CN114573269A
